An imide organic molecule modified regenerated manganese dioxide composite material, a preparation method and application thereof

CN122889882APending Publication Date: 2026-10-09BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611205814.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]然而,现有技术中利用酰亚胺类有机分子对废旧锰酸锂来源的再生二氧化锰进行界面修饰,并将其作为水系锌离子电池正极材料的研究仍较少

Benefits of technology

1、本发明以废旧锰酸锂为锰源,通过酸浸—水热反应直接获得再生β-MnO2,减少了锰盐中间产物分离及再次合成的步骤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889882A_ABST
    Figure CN122889882A_ABST
Patent Text Reader

Abstract

The application relates to the fields of resource utilization of waste lithium ion batteries and aqueous zinc ion battery materials, and discloses a method for regenerating manganese dioxide by using imide organic molecules. After the waste lithium manganate is discharged, disassembled and heat treated, regenerated beta-MnO2 is obtained through acid immersion-hydrothermal reaction, and interface modification of the regenerated beta-MnO2 is carried out by using imide organic molecules. The obtained composite material can inhibit Mn 2+ dissolution and structure degradation, improve interface ion transmission, and thus improve the specific capacity, rate performance and cycle stability of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of waste lithium-ion battery resource utilization and aqueous zinc-ion battery cathode materials, specifically relating to an imide-based organic molecule modified recycled manganese dioxide composite material, its preparation method and application. Background Technology

[0002] With the rapid development of electric vehicles and portable electronic devices, the amount of spent lithium-ion batteries is increasing rapidly. Spent lithium manganese oxide cathode materials contain valuable metals such as lithium, manganese, nickel, and cobalt, and have high resource recycling value. Among them, lithium manganese oxide is widely used in power batteries and energy storage batteries due to its low cost, good safety performance, and high environmental compatibility. Therefore, the resource recycling and high-value utilization of spent lithium manganese oxide is of great significance.

[0003] Existing methods for recycling spent lithium-ion batteries mainly include pyrometallurgical and hydrometallurgical processes. Pyrometallurgical processes are highly adaptable and can handle large volumes, but they typically require high-temperature roasting or smelting, resulting in high energy consumption. Components such as lithium can easily enter the slag, requiring further processing. Traditional hydrometallurgical processes, while achieving high metal leaching rates, often involve multiple steps of acid leaching, extraction, precipitation, and refining, leading to a lengthy process and significant acid and alkali consumption and wastewater treatment burdens. Therefore, developing a short-process, low-secondary-pollution resource utilization route that can directly produce high-value-added functional materials is an important direction in the field of spent lithium manganese oxide recycling.

[0004] Manganese dioxide (MDC) possesses advantages such as low cost, wide availability, and high theoretical specific capacity, making it suitable as a cathode material for aqueous zinc-ion batteries. Converting manganese resources from waste lithium manganese oxide into recycled MDC can increase the added value of the recycled product. However, recycled MDC is prone to direct contact with the electrolyte during charge and discharge, leading to manganese dissolution, interfacial side reactions, and crystal structure degradation, resulting in increased electrode polarization, capacity decay, and decreased cycle stability. While modification methods such as element doping, conductive material composites, and inorganic coating can improve its performance, some methods suffer from complex preparation steps, high processing temperatures, or potential alteration of the MDC's bulk structure.

[0005] Imide organic compounds typically contain two carbonyl groups and a cyclic imide structure, exhibiting strong dipolarity and interfacial interaction capabilities. The carbonyl oxygen and nitrogen-containing sites in the imide groups can interact with manganese, oxygen species, or surface hydroxyl groups on the manganese dioxide surface through coordination, electrostatic adsorption, or hydrogen bonding, allowing organic molecules to adhere to the manganese dioxide surface. The resulting organically modified interface is expected to reduce direct contact between the active material and the electrolyte, regulate interfacial ion transport and solvation environment, and inhibit the continuous dissolution of manganese species. Furthermore, phthalimides, N-hydroxyphthalimides, succinimidides, and N-iodosuccinimidides possess similar imide skeletons, providing a variety of structural options for controlling the interfacial properties of regenerated manganese dioxide.

[0006] However, existing technologies for using imide-based organic molecules to modify the interface of recycled manganese dioxide from waste lithium manganese oxide and applying it as a cathode material for aqueous zinc-ion batteries are still limited. Therefore, it is necessary to develop a method for modifying recycled manganese dioxide with imide-based organic molecules to improve interface stability, inhibit manganese dissolution, and enhance electrochemical performance while preserving its main crystal structure as much as possible, thereby achieving high-value utilization of manganese resources from waste lithium manganese oxide. Summary of the Invention

[0007] This invention uses waste lithium manganese oxide as a manganese source to prepare regenerated β-MnO2, and employs organic molecules with imide ring structures to modify its interface, constructing an imide-based organic molecule / regenerated manganese dioxide composite interface for use in high-performance aqueous zinc-manganese batteries. The imide-based organic molecules include one or more of phthalimide (Pth), N-hydroxyphthalimide (NHPI), succinimide (SI), and N-iodosuccinimide (NIS).

[0008] The first aspect of this application provides a method for preparing an imide-based organic molecule-modified regenerated manganese dioxide composite material. The method includes pretreatment of waste batteries, acid leaching-hydrothermal direct regeneration of MnO2, and organic molecule modification of the interface.

[0009] Step 1: Safely discharge, disassemble, and pre-treat used lithium manganese oxide batteries to obtain lithium manganese oxide positive electrode active material; Step 2: Mix the lithium manganese oxide positive electrode active material with an acid solution and carry out an acid leaching-hydrothermal reaction under closed conditions to allow the lithium component to enter the liquid phase and the manganese component to be converted into solid manganese dioxide. Step 3: The obtained manganese dioxide solid is separated, washed, and dried to obtain regenerated β-MnO2; Step 4: The regenerated β-MnO2 is compounded with an organic compound having an imide ring structure, so that the organic compound is loaded on the surface and / or interparticle spaces of the regenerated β-MnO2 to obtain an imide-based organic molecule modified regenerated manganese dioxide composite material.

[0010] Preferably, the waste lithium manganese oxide positive electrode active material is lithium manganese oxide powder obtained after removing the current collector, separator and other inactive components.

[0011] Preferably, the safe discharge is performed using an aqueous NaCl solution, and the discharge termination voltage is not higher than 0.1 V.

[0012] Preferably, the heat treatment temperature is 300–600 °C and the time is 0.5–5 h. More preferably, the heat treatment is carried out at 400 °C for 1 h.

[0013] Preferably, the acid solution is selected from one or more of sulfuric acid, hydrochloric acid, and nitric acid.

[0014] Preferably, the concentration of the acid solution is 0.5–5 mol / L.

[0015] Preferably, the solid-liquid ratio of the lithium manganese oxide powder to the acid solution is 1 g: (5-30) ml.

[0016] Preferably, the acid leaching-hydrothermal reaction temperature is 100–220 °C, and the reaction time is 6–48 h.

[0017] Preferably, the imide organic compound has at least one imide ring structure and at least two carbonyl functional groups.

[0018] Preferably, the imide organic compound is selected from one or more of phthalimide (Pth), N-hydroxyphthalimide (NHPI), succinimide (SI), and N-iodosuccinimide (NIS).

[0019] Preferably, the imide organic compound is loaded onto regenerated β-MnO2 by impregnation, stirring adsorption, ultrasonic dispersion, mechanical grinding, ball milling, or a combination thereof.

[0020] Preferably, the imide organic compound has a mass percentage of 0.1 to 30 wt.% relative to the regenerated β-MnO2.

[0021] As an optional resource utilization step, the lithium-containing liquid obtained from the acid leaching-hydrothermal reaction can be subjected to impurity removal and phosphate precipitation treatment to obtain Li3PO4. This lithium-containing liquid treatment process is not a necessary step in the imide-based organic molecule modified regenerated manganese dioxide composite material of the present invention.

[0022] The second aspect of this application provides an imide-based organic molecule-modified regenerated manganese dioxide composite material.

[0023] The composite material comprises a recycled β-MnO2 matrix and an imide-based organic modification component located on the surface of the recycled β-MnO2 and / or in the interparticle spaces.

[0024] Preferably, the imide-based organic modification component comprises at least one imide ring structure and at least two carbonyl functional groups.

[0025] Preferably, the imide-based organic modifying component is selected from one or more of Pth, NHPI, SI, and NIS.

[0026] Preferably, the composite material retains the β-MnO2 main crystalline phase.

[0027] Preferably, the imide organic molecules bind to the regenerated β-MnO2 surface through coordination, electrostatic adsorption, hydrogen bonding, or a combination thereof.

[0028] The third aspect of this application provides the use of the imide-based organic molecule-modified regenerated manganese dioxide composite material as a positive electrode active material for aqueous zinc-manganese batteries.

[0029] The aqueous zinc-manganese battery can be assembled using a zinc negative electrode, a separator, and an aqueous electrolyte containing zinc salts. The aqueous electrolyte may also contain manganese salts.

[0030] The electrode preparation, assembly method, and testing conditions of the battery can employ conventional techniques in the field and do not constitute a core limitation of this invention. The molar concentration of the manganese sulfate is 0.03–0.5 mol / L, and the molar concentration of the zinc sulfate is 0.05–4 mol / L. The negative electrode of the battery is a zinc foil. The thickness of the zinc foil is 30–100 micrometers, and it is sealed and assembled into a CR2032 battery under a pressure of 30–70 MPa for electrochemical performance testing.

[0031] The technical solution of this application has the following advantages compared with the prior art: 1. This invention uses waste lithium manganese oxide as the manganese source and directly obtains regenerated β-MnO2 through acid leaching-hydrothermal reaction, reducing the steps of separating and resynthesizing manganese salt intermediate products.

[0032] 2. The present invention further employs imide organic molecules to modify the interface of regenerated β-MnO2, thereby realizing the transformation of waste manganese resources from recycled products into functional electrode materials.

[0033] 3. Imidine organic molecules contain a dicarbonyl group and a polar imide ring structure, which can form interfacial interactions with manganese, oxygen species or surface hydroxyl groups on the surface of regenerated β-MnO2.

[0034] 4. The formed organic / inorganic composite interface can reduce the direct contact between regenerated β-MnO2 and the electrolyte, which is beneficial to suppressing manganese dissolution and interfacial side reactions, and improving the interfacial stability of the material.

[0035] 5. The introduction of organic molecules does not significantly damage the main crystal phase of regenerated β-MnO2, and can improve the rate performance, cycle stability and surface control kinetics of the material.

[0036] 6. Pth, NHPI, SI, and NIS have different cyclic skeletons and N-position substituents, which can be used to adjust the interfacial properties of regenerated β-MnO2. Among them, the Pth-modified sample exhibits better overall electrochemical performance.

[0037] 7. The organic modification process of the present invention can be carried out by low-temperature composite methods such as impregnation, grinding or ball milling. The process conditions are mild and have the potential for further scale-up preparation.

[0038] 8. The lithium-containing liquid obtained from acid leaching-hydrothermal reaction can be further used to prepare Li3PO4, thereby achieving additional recovery of lithium resources. Attached Figure Description

[0039] Figure 1 This is a schematic diagram of the process for preparing imide-based organic molecule-modified recycled manganese dioxide composite materials using waste lithium manganese oxide as a manganese source according to the present invention. Figure 2 X-ray diffraction pattern for the recovery of Li3PO4 and comparison with standard card PDF#97-001-0257; Figure 3 X-ray diffraction patterns of phthalimide Pth, recycled β-MnO2, and MnO2@Pth composite materials; Figure 4 Scanning electron microscope image and surface distribution diagram of Mn and O elements for regenerated β-MnO2; Figure 5 Scanning electron microscope image of the composite cathode material MnO2@Pth and surface distribution diagram of Mn, O, C, and N elements; Figure 6 Here are schematic diagrams of the structures of four preferred imide organic compounds; Figure 7 Phthalimide, N-hydroxyphthalimide, succinimide, and N-iodosuccinimide were present at 0.2 A g. -1 Cyclic performance at current density; Figure 8 Phthalimide, N-hydroxyphthalimide, succinimide, and N-iodosuccinimide at 0.5 A g -1 Cyclic performance at current density; Figure 9 The constant current charge-discharge curves and rate performance at different current densities for regenerating β-MnO2 and MnO2@Pth were obtained. Figure 10 Cyclic voltammetry curves of regenerated β-MnO2 and MnO2@Pth at different scan rates; Figure 11 Fitting plots of b-values ​​for regenerated β-MnO2 and MnO2@Pth at different scan rates; Detailed Implementation To make the objectives, technical solutions, and technical effects of this invention clearer, the invention will be further described below with reference to embodiments. The described embodiments are only some embodiments of this invention and are not intended to limit the scope of protection of this invention.

[0040] Unless otherwise stated, all raw materials and reagents used in the examples are commercially available, and the water used is deionized water. Experimental and testing methods not specifically described can be performed using conventional methods in the art.

[0041] Example 1: Pretreatment and composition analysis of waste lithium manganese oxide cathode material Used lithium manganese oxide batteries were safely discharged by immersing them in a NaCl aqueous solution until the battery voltage dropped below 0.1 V. After discharge, the batteries were disassembled, and the positive electrode, negative electrode, and separator were separated. The positive electrode containing the active material was collected.

[0042] The positive electrode sheet was placed in a muffle furnace and heat-treated at 400 °C for 1 h to remove the PVDF binder and carbonaceous conductive agent. After cooling, waste LiMn2O4 powder was obtained.

[0043] 0.0167 g of sample was weighed and diluted to 50 mL. Li and Mn were determined by inductively coupled plasma atomic absorption spectrometry (ICP-AES). The concentration of the Li test solution was 10.04 mg / L, and the calculated Li content in the sample was 3.006 wt.%. The concentration of the Mn test solution was 6.89 mg / L. After a 10-fold dilution correction, the original concentration was 68.93 mg / L, and the calculated Mn content in the sample was 20.638 wt.%.

[0044] Example 2: Acid leaching-hydrothermal regeneration of β-MnO2 and acquisition of lithium-containing leachate Weigh 2.5 g of the waste LiMn2O4 powder obtained in Example 1, add 25 mL of 2 mol / L H2SO4, transfer the mixture to a 50 mL polytetrafluoroethylene-lined reactor, seal it, put it into a stainless steel jacket and tighten it, and react it at 200 °C for 24 h.

[0045] After the reaction is complete, allow it to cool naturally to room temperature. Transfer the reaction mixture to a centrifuge tube and centrifuge at 10,000 r / min for 5 min. Collect the supernatant as a lithium-containing leaching solution for later use.

[0046] Deionized water was added to the solid for redispersement, and the mixture was centrifuged and washed under the same conditions. This process was repeated three times until the supernatant was clear and transparent. The resulting solid was dried at 60 °C to constant weight to obtain regenerated β-MnO2.

[0047] Example 3: Recovery of Li3PO4 Precipitation from Lithium-Containing Liquid A 1 mol / L NaOH solution was slowly added to the lithium-containing leachate obtained in Example 2 to adjust the pH of the system to 10, causing residual manganese and other impurities to form a brown precipitate.

[0048] The precipitate was removed by vacuum filtration to obtain a clear lithium-containing filtrate. The filtrate was then evaporated and concentrated, and a saturated Na3PO4 solution was slowly added dropwise while stirring until no more white precipitate formed in the supernatant.

[0049] The white solid was collected, washed three times with deionized water, and dried to constant weight in a 60 °C oven. The obtained product, Li3PO4, matched the standard card PDF#97-001-0257. The mass was 0.338 g, and the lithium recovery rate was 92.8%.

[0050] Example 4: Preparation of Phthalimide-Modified Regenerated MnO2 The regenerated β-MnO2 and phthalimide obtained in Example 2 were weighed, wherein the mass percentage of Pth relative to the regenerated MnO2 was 16.7%. The two were combined by grinding under N-methylpyrrolidone (NMP) conditions for 30 min to load Pth onto the surface of MnO2 nanorods; then dried in a vacuum oven for 4 hours to obtain the MnO2@Pth composite material.

[0051] XRD results show that MnO2@Pth retains the β-MnO2 host crystalline phase; SEM and EDS surface scanning show that Mn, O, and C elements are co-located in the composite particle region, proving that Pth has been introduced into the surface of the regenerated MnO2.

[0052] Example 5: Optional Modification Methods for Other Imidamine Organic Compounds Under the same or similar composite conditions as in Example 4, phthalimide can be replaced with N-hydroxyphthalimide, succinimide, or N-iodosuccinimide to form corresponding NHPI-modified, SI-modified, or NIS-modified regenerated MnO2. All compounds contain a cyclic imide skeleton and a dicarbonyl structure, and can be used to construct organic interface layers through impregnation, adsorption, grinding, ball milling, or combinations thereof.

[0053] The organic molecules mentioned above all contain an imide ring and a dicarbonyl structure, but their aromatic ring structures and N-position substituents are different, which can have different regulatory effects on the interfacial properties of regenerated β-MnO2.

[0054] Example 6: Cathode preparation and aqueous zinc-ion battery assembly MnO2@Pth, multi-walled carbon nanotubes and PVDF were mixed in a mass ratio of 7:2:1, and NMP was added to make a uniform slurry. The slurry was coated onto carbon cloth and then punched to obtain a positive electrode sheet after being vacuum dried at 70 °C for 6 h.

[0055] A coin-type aqueous zinc-ion battery was assembled using metallic zinc as the negative electrode, glass fiber or other aqueous battery membrane as the separator, and a mixed aqueous solution of 2 mol / L ZnSO4 and 0.2 mol / L MnSO4 as the electrolyte.

[0056] The positive electrode active material loading is 1.6 mg cm⁻¹ -2 The electrolyte volume was 150 μL, and the test voltage window was 0.8-1.8V.

[0057] Comparative Example 1: Regenerated β-MnO2 without imide organic modification Using the regenerated β-MnO2 obtained in Example 2 as the positive electrode active material, an aqueous zinc-ion battery was assembled according to the same electrode formulation, active material loading, electrolyte composition and battery assembly conditions as in Example 6, to evaluate the effect of the organic interface layer on zinc storage performance.

[0058] Table 1 shows the test results of Li and Mn element content in waste lithium manganate. Material characterization and performance testing: Figure 1 This is a schematic diagram of the process for preparing imide-based organic molecule-modified recycled manganese dioxide composite materials using waste lithium manganese oxide as a manganese source according to the present invention.

[0059] Figure 2 X-ray diffraction pattern for the recovered Li3PO4. The main diffraction peaks of the obtained product are basically consistent with the Li3PO4 standard card (PDF#97-001-0257), and no obvious impurity peaks were observed, indicating that Li3PO4 can be obtained from the lithium-containing solution after purification and phosphate precipitation. This result demonstrates that lithium resources can be used as an additional recovery product of the process of this invention.

[0060] Figure 3The X-ray diffraction patterns of phthalimide (Pth), recycled β-MnO2, and MnO2@Pth composite materials are shown. As can be seen from the figures, each diffraction peak of the recycled product corresponds to the standard crystalline phase of β-MnO2, indicating that the method described in this application can successfully convert the manganese component in waste lithium manganese oxide into well-crystallized β-MnO2. Furthermore, after phthalimide coating, the MnO2@Pth composite material still maintains the main β-MnO2 crystal structure, and its diffraction peak positions remain basically unchanged, with only slight changes in local peak intensity or background signal. This indicates that the introduction of organic molecules did not destroy the main crystalline phase of MnO2, but was successfully constructed on the surface of recycled MnO2 through surface coating, forming an organic / inorganic composite structure.

[0061] Figure 4 The images show scanning electron microscope (SEM) images of regenerated β-MnO2 and the surface distribution diagrams of Mn and O elements. As can be seen from the figures, the regenerated β-MnO2 exhibits a relatively uniform micro / nano particle morphology with a relatively uniform particle size distribution, and no obvious large-size agglomeration was observed. The surface distribution results show that Mn and O elements are uniformly distributed throughout the particle region, indicating that the obtained regenerated MnO2 has a uniform composition and a complete manganese-oxygen framework, providing a stable support structure for the subsequent construction of the organic interface layer.

[0062] Figure 5 Scanning electron microscope (SEM) images and elemental distribution diagrams of the composite cathode material MnO2@Pth are shown. As can be seen from the figures, after phthalimide modification, the overall morphology of the MnO2 matrix remains intact, without significant structural collapse or particle aggregation. The elemental distribution results show that, except for Mn and O, C and N elements are uniformly distributed on the surface of the MnO2 particles, consistent with the composition of Pth molecules, indicating that phthalimide has been successfully loaded onto the surface of the regenerated MnO2 and formed a relatively uniform organic coating layer. This organic interface layer is beneficial for regulating the electrode / electrolyte interface microenvironment, improving the structural stability of the material, and inhibiting manganese dissolution during cycling.

[0063] Figure 6 The diagram shows the structures of four preferred imide organic compounds. As can be seen from the diagram, this application preferably uses organic compounds with imide ring structures as interface modification molecules for regenerated MnO2, including phthalimide (Pth), N-hydroxyphthalimide (NHPI), succinimide (SI), and N-iodosuccinimide (NIS). All of these compounds possess imide functional groups, which can form stable interactions with the MnO2 surface, thereby improving interfacial stability and the ion transport environment. Among them, Pth has a large conjugated aromatic ring structure, which can further enhance the interfacial stabilizing effect, and is therefore the preferred embodiment of this application.

[0064] Figure 7Phthalimide, N-hydroxyphthalimide, succinimide, and N-iodosuccinimide were present at 0.2 A g. - ¹Cycling performance at current density. As shown in the figure, at 0.2 A g… -1 At different current densities, regenerated MnO2 modified with different imide organic molecules all exhibited superior cycle stability compared to the unmodified material. Among them, the phthalimide-modified sample showed the highest reversible capacity and best capacity retention, followed by N-hydroxyphthalimide, N-iodosuccinimide, and succinimide. These results indicate that imide organic molecules can improve the cycle stability of the regenerated MnO2 cathode to varying degrees, with Pth, possessing an aromatic conjugated structure, showing the most significant effect in improving electrode stability.

[0065] Figure 8 Phthalimide, N-hydroxyphthalimide, succinimide, and N-iodosuccinimide at 0.5 A g -1 Cycling performance at current densities. As shown in the figure, under high current density conditions, the cathode materials modified with various imide organic molecules still maintain good cycling stability. Among them, the Pth-modified sample exhibits the smallest capacity decay and excellent rate cycling stability. The results indicate that the imide organic interface modification strategy adopted in this application can effectively improve the structural stability and electrochemical reversibility of regenerated MnO2 under high rate conditions.

[0066] Figure 9 The constant current charge-discharge curves and rate performance at different current densities of regenerated β-MnO2 and MnO2@Pth are presented. As shown in the figures, MnO2@Pth exhibits a more stable charge-discharge plateau and a lower polarization voltage during charge-discharge, indicating that the electrode reaction kinetics are improved after Pth modification. Furthermore, at different current densities, MnO2@Pth demonstrates a higher discharge specific capacity than unmodified β-MnO2, and recovers a higher capacity after returning to the initial current density. This indicates that the Pth interface layer not only improves the rate performance of the material but also enhances the reversibility and stability of the electrode structure.

[0067] Figure 10 Cyclic voltammetry curves of β-MnO2 and MnO2@Pth at different scan rates were obtained. As shown in the figure, both materials maintained good redox peak shapes with increasing scan rate, but the MnO2@Pth sample exhibited a larger integrated area and clearer redox peaks, indicating higher electrochemical activity and faster charge storage capacity. Simultaneously, its peak shift was smaller, suggesting that Pth modification can reduce electrode polarization and improve Zn²⁺. + and H + This improves the transport efficiency and promotes electrode reaction kinetics.

[0068] Figure 11 The figure shows the b-value fitting graphs for regenerated β-MnO2 and MnO2@Pth at different scan rates. As can be seen from the figure, the corresponding b-values ​​were obtained based on the fitting relationship between peak current and scan rate at different scan rates. The b-value of the MnO2@Pth sample is generally higher than that of unmodified β-MnO2, indicating that its energy storage process has a higher proportion of surface pseudocapacitance contribution, further reducing ion diffusion resistance and significantly improving charge transport kinetics. These results further demonstrate that the phthalimide-constructed organic interface layer can effectively optimize the energy storage process of regenerated MnO2, improve the rate performance and cycle stability of the material, and provide an effective technical approach for the high-value utilization of recycled lithium manganese oxide cathode materials.

Claims

1. An imide-based organic molecule-modified regenerated manganese dioxide composite material and its preparation method, characterized in that, Includes the following steps: Step 1: Safely discharge, disassemble, and pre-treat used lithium manganese oxide batteries to obtain lithium manganese oxide positive electrode active material; Step 2: Mix the lithium manganese oxide positive electrode active material with an acid solution and carry out an acid leaching-hydrothermal reaction under closed conditions to allow the lithium component to enter the liquid phase and the manganese component to be converted into solid manganese dioxide. Step 3: Separate, wash and dry the obtained manganese dioxide solid to obtain regenerated β-MnO2; Step 4: The regenerated β-MnO2 is combined with an organic compound having an imide ring structure, so that the organic compound is loaded on the surface and / or interparticle gaps of the regenerated β-MnO2 to obtain an imide-based organic molecule modified regenerated manganese dioxide composite material.

2. The method according to claim 1, characterized in that, In step one, NaCl aqueous solution is used to safely discharge the waste lithium manganese oxide batteries. The positive electrode obtained after disassembly is heat-treated at 300-600 °C for 0.5-6 h to remove polymer binders and carbonaceous conductive agents.

3. The method according to claim 1, characterized in that, The acid solution is selected from one or more of sulfuric acid, hydrochloric acid, and nitric acid; the concentration of the acid solution is 0.5–5 mol / L; the acid leaching-hydrothermal reaction temperature is 100–220 °C, and the reaction time is 6–48 h.

4. The method according to claim 1, characterized in that, The resulting regenerated β-MnO2 was washed and dried at 40–100 °C to constant weight.

5. The method according to claim 1, characterized in that, The organic compound having an imide ring structure contains at least one imide ring structure and at least two carbonyl functional groups.

6. The method according to claim 5, characterized in that, The imide organic compound is selected from one or more of phthalimide, N-hydroxyphthalimide, succinimide and N-iodosuccinimide.

7. The method according to claim 1, characterized in that, The organic compound is loaded onto the surface of regenerated β-MnO2 by impregnation, adsorption, ultrasonic dispersion, mechanical grinding, ball milling or a combination thereof, and the mass percentage of the organic compound relative to the regenerated β-MnO2 is 0.1 to 30 wt.%.

8. A composite material of recycled manganese dioxide modified with imide-based organic molecules, characterized in that, It includes a recycled β-MnO2 matrix obtained from the conversion of waste lithium manganese oxide, and an imide-based organic modification layer located on its surface and / or between particles.

9. The composite material according to claim 8, characterized in that, The imide-based organic modified layer is formed from one or more of phthalimide, N-hydroxyphthalimide, succinimide and N-iodosuccinimide.

10. The application of the imide-based organic molecule modified regenerated manganese dioxide composite material according to claim 8 or 9 in the positive electrode of an aqueous zinc-ion battery.